Ambulatory level and asymmetrical weight bearing after stroke affects bone loss in the upper and lower part of the femoral neck differently: bone adaptation after decreased mechanical loading. - Jørgensen, L; Crabtree, N; Reeve, J; Jacobsen, B (2000)
The aim of this 1-year prospective study of acute stroke patients was to determine the effects of walking and asymmetrical weight bearing on the loss of bone mineral in the upper and lower femoral neck. Forty patients were followed. Eight remained unable to walk, whereas 32 relearned to walk independently within 7 months (12 shortly after the stroke, 15 by 2 months, 5 by 7 months). Bone mineral density (BMD) was measured in the proximal femur within the first week after stroke and 1 year later; regional BMD changes were computed for the lower and upper femoral neck. The lower part of the femoral neck is mainly influenced by compressive stresses of the hip, the upper part by tensile stresses during walking. When comparing mean BMD loss in groups of patients according to when they relearned to walk, a statistically significant trend in BMD loss was found in the lower femoral neck on both the paretic and nonparetic sides (p < 0.01 and p = 0.01, respectively), whereas, for the upper femoral neck, no significant trend was seen (p >/= 0.1). In addition, the body weight distribution during standing was assessed by use of a force-plate in 38 patients who could stand independently at the 7 month evaluation. The only significant correlation between changes in BMD and asymmetrical weight bearing was found in the lower femoral neck on the paretic side (r = 0.6, p < 0.001). In conclusion, this study shows that the reduction in BMD in the femoral neck occurs mainly in the lower part of the neck and on the paretic side. The BMD loss depended on when or if the patients relearned to walk, but also on the amount of body weight born on the paretic leg. Thus, measuring the lower part of the femoral neck gives a better estimate of the impact of gait and weight bearing than measuring the total femoral neck.